Uromodulin biology and pathophysiology--an update - Vyletal, Petr; Bleyer, Anthony J; Kmoch, Stanislav (Kidney & blood pressure research, 2010)
Uromodulin (UMOD) is a glycoprotein expressed on the luminal surface of the apical membrane of renal tubular epithelial cells forming the thick ascending limb of Henle. Here, UMOD forms filamentous structures probably ensuring water impermeability and the countercurrent gradient. The multidomain structure, cellular topology of UMOD and clinical consequences associated with UMOD dysfunction, however, suggest that it may be involved in other biological processes such as receptor-mediated endocytosis, mechanosensation of urinary flow, Wnt-signaling, cell cycle regulation and planar cell polarity. A specific, but as yet unidentified, protease(s) releases UMOD into the urine, where it probably contributes to colloid osmotic pressure, retards passage of positively charged electrolytes, prevents urinary tract infection and modulates formation of supersaturated salts and their crystals. UMOD expression, biosynthesis and excretion are regulated in a complex manner, and dysregulation is found in a wide range of pathological conditions. It is strongly reduced or absent in cases with mutations in UMOD, renin, HNF1B and other genetic disorders causing autosomal dominant hyperuricemic nephropathy. In contrast, elevated UMOD excretion may be associated with, and thus predictive of, chronic kidney disease. UMOD analysis is therefore of importance in all conditions with renal involvement and may be useful in the proper classification of renal diseases.
Keywords: uromodulin; mutace; hyperurikemie; Animals; Uromodulin; Humans; Mutation; lidé; nemoci ledvin; Kidney Diseases; zvířata; Hyperuricemia